Block copolymer binders with hard and soft segments for scalable fabrication of sulfide‐based all‐solid‐state batteries. Issue 4 (23rd February 2022) - Lee, Jieun; Choi, Jang Wook
Abstract: Sulfide‐based all‐solid‐state batteries (ASSBs) have attracted much attention owing to their superior safety and potentially high‐energy density. Nevertheless, sulfide‐based ASSBs suffer from limited performance in terms of their cycle life and rate capability, which is closely related to interfacial degradation during cycling. Another weakness is the absence of manufacturing protocols. Having noted that the binder can play a pivotal role in both the cell performance and scale‐up, here, we report poly(1, 2‐butadiene)‐ b ‐poly(methyl methacrylate) (PBD‐ b ‐PMMA) block copolymers as the binders. At the optimal ratio, the soft PBD segments and hard PMMA segments work synergistically to strengthen adhesion among particles in the electrode and introduce elasticity in the binder network, enabling the key battery performance indicators to be improved markedly. The systematic study also reveals the importance of the microscopic distributions of these two segments. This study signifies the appropriate combination of adhesion and elasticity in designing binders for sulfide‐based ASSBs. Abstract : The block copolymers consisting of the polybutadiene (PBD) soft segments and poly(methyl methacrylate) (PMMA) hard segments are reported as binders for sulfide‐based all‐solid‐state batteries. The PBD and PMMA segments are responsible for the elasticity of the network and the adhesion with the active material, respectively. At the optimal ratio, the hard and soft segments cooperate synergistically for the best electrochemical performance.